The Methodology of Imam Bukhārī in Al Tārīkh Al Kabīr for Criticism, Praise and Biographies of Narrators - Muhammad Noman; Muhammad Ikramullah; Junaid Akbar (Journal of Islamic and Religious Studies, 2019)
Muḥadithīn have played a dynamic role in the preservation and compilation of Ḥadīth of the Prophet (SAW). Among them the contribution of Imam Bukhārī is unavoidable and remarkable in the field of Ḥadīth and its sciences. Since, he is known “Hafiz and Compiler” and considered as “Imam” and “authority” in the field of both higher and lower criticism. His book "Al-Tārīkh al Kabīr" (08 volumes) is considered as one of the ancient books in field of Ḥadīth and its sciences. This paper aims to describe the methodology of Imam Bukhārī in Al-Tārīkh al Kabīr. He described the biography of thirteen thousand seven hundred and seventy nine only (13779) in alphabetic order. Although his methodology was to mention names of the narrators alphabetically, but in respect with the Prophet (SAW), he gave place to eleven narrators among the companion whom names were started with the names of “Muhammad”. In the Methodology of Imam Bukhārī (RA), it is found that either the narrators are rejected or given authenticity, on the basis of not only his own examinations but he relied on the sayings of other Muḥadithīn as well. It is also pertinent to mention that he awarded degree to a little number of the narrators while left over most of the narrators undecided, because the main objective of the book was to portray the biographies of the narrators rather to make analysis of all the narrators.